Persistent identifiers: building the plane as we fly it: Pablo De-Castro - De-Castro, Pablo (Anuario ThinkEPI, 2023)
Persistent identifiers (PIDs) may be defined as permanent and globally unique references to any kind of digital or physical entity. The area of PIDs is currently experiencing a remarkable development. There is a whole range of emerging PIDs on top of the already consolidated ones such as digital object identifiers (DOIs) and ORCIDs for authors. Among the emerging PIDs, it is worth mentioning grant identifiers issued by research funders, identifiers for research equipment and facilities, organizational identifiers (Org IDs), and identifiers for physical geosamples (IGSN). Some reflections are shared here on the gradual evolution in the discipline and the advisability of having strategies in place for the adoption and use of this technology..
Keywords: Persistent identifiers (PIDs); Landscape analysis; Case studies; Level of maturity; National PID strategies